Boko Haram Insurgency and Nigeria’s Foreign Policy in the Lake Chad Region - Kashere, Dauda Yahaya; Ibrahim, Ibrahim Aliyu; Garba, Yakubu (Kashere Journal of Politics and International Relations, 2025)
This paper examined the implications of Boko Haram insurgency on Nigeria’s foreign policy in the Lake Chad region. The study purposely evaluated how Nigeria’s foreign policy have been jeopardized, disrupted and negatively affected by the activities of Boko Haram insurgency and terrorism in the region. The study is purely qualitative in nature and used secondary data. The data were analyzed thematically through content analysis. The linkage theory was adopted in the analysis of this work. The findings of this study revealed that the emergence of Boko Haram insurgency and terrorist acts plummeted Nigeria’s relevance in the Lake Chad region and the international community. The insurgents’ activities led to the displacement of people from Borno, Yobe and Adamawa states in the form of Internally Displaced Persons (IDPs) fleeing to safer havens within the nation and refugees were fleeing to neighbouring countries like Niger, Chad and Cameroun in the region. It is therefore recommended among others that, Nigerian government should improve the socioeconomic conditions of Nigerians to dissuade them from all forms of recruitment to Boko Haram sect. Nigerian government should deepen collaboration with the governments of Member States of the Lake Chad Basin Commission to devise strategies to meaningfully address the Boko Haram insurgency through military and non-military approaches.